2014
DOI: 10.3758/s13414-014-0648-9
|View full text |Cite
|
Sign up to set email alerts
|

Attention meets binding: Only attended distractors are used for the retrieval of event files

Abstract: Response-irrelevant stimuli can be encoded with, and later on retrieve, a response given to a relevant stimulus, an effect that is called distractor-response binding. In three experiments using a prime-probe design, we investigated whether the allocation of attention modulates the processes contributing to distractor-response binding. Participants identified letters via keypresses while attending to one of two sets of simultaneously presented but response-irrelevant number stimuli. In different experiments, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 72 publications
8
77
0
Order By: Relevance
“…Figure 3 is an example for data collected by Frings, Rothermund and Wentura (2007). Figure 4 summarizes the distractor-response binding effects of 33 experiments in different modalities 9,[18][19][20][21][22][23][24][27][28][29][30] . The effects become larger with more difficult tasks and thus with longer response times.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 is an example for data collected by Frings, Rothermund and Wentura (2007). Figure 4 summarizes the distractor-response binding effects of 33 experiments in different modalities 9,[18][19][20][21][22][23][24][27][28][29][30] . The effects become larger with more difficult tasks and thus with longer response times.…”
Section: Representative Resultsmentioning
confidence: 99%
“…has on response integration with the distractor is of interest, this factor can be varied on the prime, while it is held constant on the probe. For an analysis of an influence on response retrieval, the factor can be manipulated on the probe while being kept constant on the prime 22,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the findings of Rothermund et al, it has been shown that distractor stimuli at encoding can modulate repetition priming at retrieval even when the stimulus remains a distractor (Frings, Moeller, & Rothermund, 2013;Frings, Rothermund, & Wentura, 2007). Such distractor-to-distractor effects suggest that, under certain experimental conditions, attention and task relevance are not necessary for both the encoding and the retrieval of S-R bindings (though see Moeller & Frings, 2014). As in the literature for attended stimuli, these studies typically utilize a classification task at retrieval (e.g., the colour of a word), typically binary (e.g., Rothermund et al, 2005), though also four distinct response options have been used (e.g., Frings et al, 2007).…”
mentioning
confidence: 99%
“…A possibly more direct link between attention and episodic memory can be taken from recent work by Moeller and Frings (2014). Here the authors wondered whether the binding of responses to targets as part of their event files also reach distractors.…”
Section: Binding Of Target and Distractor Properties In An Episodic Tmentioning
confidence: 99%